Terencjusz według Ewy Skwary - Kocur, Mirosław (Przestrzenie Teorii, 2017)
Review of an outstanding monograph on Terence and his comedies by Ewa Skwara, the finest Polish scholar of early Latin and ancient Roman theatre.